Multiwavelength analysis of OH Megamaser galaxies: The case of IRAS11506-3851. Issue Volume 15:Issue S359(2020) (March 2019) - Hekatelyne, Carpes P.; Storchi-Bergmann, Thaisa
Abstract: We present Multi-Object Spectrograph (GMOS) Integral Field Unit (IFU), Hubble Space Telescope (HST) and Very Large Array (VLA) observations of the inner kpc of the OH Megamaser galaxy IRAS 11506-3851. In this work we discuss the kinematics and excitation of the gas as well as its radio emission. The HST images reveal an isolated spiral galaxy and the combination with the GMOS-IFU flux distributions allowed us to identify a partial ring of star-forming regions surrounding the nucleus with a radius of ≍500 pc. The emission-line ratios and excitation map reveal that the region inside the ring present mixed/transition excitation between those of Starbursts and Active Galactic Nuclei (AGN), while regions along the ring are excited by Starbursts. We suggest that we are probing a buried or fading AGN that could be both exciting the gas and originating an outflow.